2020
DOI: 10.1186/s13690-020-00404-3
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ food choices, understanding and perceptions in response to different front-of-pack nutrition labelling systems in Belgium: results from an online experimental study

Abstract: Background Front-of-pack nutrition labels (FoPLs) are increasingly implemented by governments internationally to support consumers to make healthier food choices. Although the Nutri-Score FOPL has officially been implemented in Belgium since April 2019, no study has been conducted before its implementation to compare the effectiveness of different FOPLs. Methods The aim of this study was to compare food choices, objective understanding and percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 18 publications
(22 reference statements)
6
37
0
Order By: Relevance
“…Compared to the RIs, the Nutri-Score was the FoPL that produced the largest increase in participants' ability to correctly rank the nutritional quality of products, followed by the HSR. These results are consistent with the findings based on the FOP-ICE study, where the Nutri-Score was observed as the best scheme to help participants identify the nutritional quality of products in different countries, including European countries: Belgium, Bulgaria, Denmark, France, Germany, Spain, Switzerland, the Netherlands and the United Kingdom [19,22,25,26]. Notably, similar results were observed in Spain, another Mediterranean country with a similar food context and dietary behaviors as Italy [19].…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the RIs, the Nutri-Score was the FoPL that produced the largest increase in participants' ability to correctly rank the nutritional quality of products, followed by the HSR. These results are consistent with the findings based on the FOP-ICE study, where the Nutri-Score was observed as the best scheme to help participants identify the nutritional quality of products in different countries, including European countries: Belgium, Bulgaria, Denmark, France, Germany, Spain, Switzerland, the Netherlands and the United Kingdom [19,22,25,26]. Notably, similar results were observed in Spain, another Mediterranean country with a similar food context and dietary behaviors as Italy [19].…”
Section: Discussionsupporting
confidence: 90%
“…Given the limited number of studies on understanding in advertising, the comparison was made with studies that addressed the degree of understanding of the information provided on labelling/packaging. Such studies show mixed results: while some works show an understanding of the information provided on labels [45,46], others show opposite results [56,58]. In both cases, however, the studies agree that the information needs to be improved to make it easier to understand.…”
Section: Discussionmentioning
confidence: 94%
“…A review of the literature highlights how studies on consumers' understanding of health claims largely focus on that of food packaging and labelling. The current research agenda is marked by research on the layout and location of information on the FOP (Front of Package) and its understanding by the consumer, the well-known "label effect" [40,41], narrowed to different geographical areas such as Belgium, Switzerland, Germany, France, United Kingdom and the Netherlands in Europe [42][43][44][45][46], Brazil and Mexico in Latin America [47,48], or the United States [49][50][51]; Australia and New Zealand [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…Nutri-Score rates the nutritional quality of packaged foods with five colours/letters from red (least healthy) to green (most healthy) [ 3 ]. A previous study among 1007 Belgian consumers found that Nutri-Score was the most effective FOP to inform consumers about the nutritional quality of food products, compared to other existing FOP nutrition labels [ 4 ].…”
Section: Introductionmentioning
confidence: 99%